A cost-minimization analysis of dalbavancin compared to conventional therapy for the outpatient treatment of acute bacterial skin and skin-structure infections. (4th March 2018) - Turco, Neil J; Kane-Gill, Sandra L; Hernandez, Inmaculada; Oleksiuk, Louise-Marie; D'Amico, Frank; Pickering, Aaron J
ABSTRACT: Introduction : Acute bacterial skin and skin-structure infections (ABSSSI) are common infectious diseases (ID) that often require intravenous (IV) antibiotics. Dalbavancin is a novel lipoglycopeptide antibiotic administered once that is FDA-approved for the treatment of ABSSSI. No literature is available for real-world cost-comparability relative to conventional therapy. Methods : This retrospective chart review examined adults diagnosed with ABSSSI and treated with IV antibiotics at an outpatient ID clinic after hospital discharge from January 2015 to August 2016. Patients received either dalbavancin or conventional therapy. In-hospital baseline demographics as well as outpatient clinical variables and outcomes were assessed. The primary outcome was the total ID-related cost of care per patient. A Monte Carlo probalistic sensitivity analysis was conducted. Results : One hundred and fifty-eight patients were included: 64 received dalbavancin and 94 received conventional therapy. The total ID-related cost of care per patient was greater with dalbavancin (mean $4, 561) vs conventional (mean $1, 668), p  < 0.01. In the subset of patients treated with daptomycin, the total ID-related cost (mean $5, 218) was comparable to dalbavancin (mean $4, 561). Conclusions : Dalbavancin was more costly than conventional therapy for the outpatient treatment of ABSSSI. This greater overall cost was likely driven by the higher acquisition cost of dalbavancin. Dalbavancin may be comparable to the daily use of daptomycin for ABSSSI.